Ambiguity of Interpretation in The Criminal Act of Contempt of State Institutions in The Potential Criminal Acts of Abuse of Power - Wahyuono, Firman Tri; Munawar, Said; Luhukay, Roni Sulistyanto (UNISKA LAW REVIEW, 2026)
This study examines the ambiguity of interpretation in the criminal act of contempt of state institutions in the context of potential criminal acts of abuse of power. The method used is legal research. The results show that democracy requires the guarantee of freedom of expression as a basis for public participation and a mechanism for controlling power. In this context, the criminal act of insulting state institutions becomes problematic when formulated in a multi-interpretive manner and does not comply with the principles of legality and lex certa. The ambiguity of the element of "insult" opens up wide discretion for law enforcement officials and has the potential to lead to selective law enforcement. Philosophically, state institutions as public entities cannot be equated with individuals in terms of protecting moral honor, because these institutions are formed to carry out public functions that must be open to criticism. In the new Criminal Code, the criminal threat of insulting state institutions is posed between the goal of protecting the institution and the potential for repression. The state does have an interest in maintaining the authority and function of its institutions, but disproportionate penalties risk exceeding the limits of a last resort. If applied broadly and elastically, this provision can have a chilling effect, limit the space for criticism, and open up opportunities for abuse of power.